Ankyloglossia: Diagnosis, Challenges, the Role of Frenotomy in Treatment – A Comprehensive Literature Review - Weimann, Maja; Janura, Marta; Byrska, Martyna; Barska-Kobylińska, Hanna; Przywara, Grzegorz; Biegańska , Oliwia; Biczak, Emilia (Journal of Education, Health and Sport, 2025)
Introduction Ankyloglossia is a congenital condition where a shortened sublingual frenulum restricts tongue movement, leading to breastfeeding challenges like nipple pain, poor latch, insufficient milk transfer, low infant weight gain and obstructive sleep apnea syndrome (OSAS) in children. Breastfeeding during the early months of a child's life is essential for healthy development. Aim The aim of this study is to gather information based on scientific research regarding the effectiveness and justification of performing frenotomy in newborns who have experienced breastfeeding, speech, sleep difficulties due to ankyloglossia. We also focus on other reasons for performing frenotomy in children. Material and method Multiple studies were conducted to assess the impact of frenotomy on issues related to ankyloglossia. Using PubMed, we searched for articles with the keywords "ankyloglossia" and "frenotomy" to identify publications that met our criteria. Conclusions Based on a studies full lingual frenetomy is an effective intervention for improving speech, feeding, and sleep in children with restricted tongue mobility